With respect to a family crisis (Portuguese Journal of Family Medicine and General Practice, 2006)
Adolescence is a relatively recent «phenomenon» in the history of the psychosocial development of the human being and it is by definition a period in which the distinction between normal and pathological becomes more difficult. Most of the times the family physician has difficulty in coping with the adolescent either because this age group doesnt usually seek medical visits or because this is a period of development with special biological, psychological and social characteristics (searching for a stable personality, shaping self-identity, sexual identification and achievement of intimacy and winning autonomy with progressive integration in the adults world). Lauras case, a 16 years old adolescent sent to the family physician by the psychologist of «Escola Básica 2/3 de XYZ», where the patient attends the 7th grade, is interesting because it allows to approach adolescences typical problems such as school failure, risk-taking behaviour and family functionalism. This is an adolescent without relevant former past history of disease, falloff in school performance, which became worse after a first parents separation because of her fathers extra-matrimonial relationship. In 2003 she began substance abuse and in October 2004 she revealed suicidal thoughts, with episodes of self-mutilation. The objective of the treatment plan is the disappearance of the adolescents most invalidating symptoms and improves her self-esteem (stimulating the short, medium and long time resources), so that communitarian integration can be possible without physical or psychic risks.
Keywords: Adolescence; Family Physician; School Failure; Family Functionalism; Suicidal Thoughts